U-PB ISOTOPIC AGE OF ZIRCON FROM HYBRID ROCKS OF THE KOROSTEN ANORTHOSITE-RAPAKIVI-GRANITE PLUTON - Bilan, O.; Mytrokhyn, O.; Shumlyanskyy, L.; Zagorodniy, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The authors have obtained new data on U-Pb isotopic age of zircon from hybrid rocks of the Korosten Pluton associated with the anorthositerapakivi-granite of the Ukrainian Shield rock formation. Zircon grains were separated from the sample of hybrid monzonitic gabbro, which crops out along the eastern flank of the Volodarsk-Volynsky gabbro-anorthosite massif, and from the sample of fayalite-hedenbergite-amphibole granosyenite in the form of a vein which cuts monzonitic gabbro and shows indications of the magma mingling. U-Pb age for individual zircon crystals obtained by SIMS (1760,7±4.1 Ma for monzonitic gabbro, and 1763,8±2.6 Ma for granosyenite) are interpreted as the crystallization age of the hybrid rocks that has developed at the contact zone of gabbroic rocks of the Volodarsk-Volynsky gabbro-anorthosite massif and granitic rocks of the Malin rapakivi massif. In addition, the samples of rapakivi-like granite of the marginal facies of the Malyn massif and the samples of rapakivi granite of its plutonic facies were dated by the U-Pb zircon SIMS method. It was found out that U-Pb isotopic age of the examined hybrid rocks within the analytical error corresponds to the age of rapakivi-like granite (1765,4±3.3 Ma) and rapakivi granite (1762,7±5,5 Ma) of the Malin massif as well as to the age of gabbroic rocks (1759,1±3,2 Ma) that constitute the eastern flank of the Volynsky massif. The similarity of the crystallization age of hybrid rocks in association with gabbroic and granitic rocks is consistent with the previous conclusion about the mechanism of the formation of the whole range of the Korosten Pluton hybrid rocks which assumes the magma mixing of a high temperature mafic magma with lower-temperature granitoid magma in liquid or semi-liquid state.